Akinete formation under nitrogen limitation in an invasive cyanobacterium - Ríos-Henríquez, Catalina; Weithoff, Guntram (Frontiers in Microbiology, 2025)
Invasive species are a global problem threatening the function of ecosystems. Besides prominent species, microbial invaders are considered as “invisible” and have spread over almost all continents. For such invisible, invasive cyanobacteria, akinete formation plays a key role in species dispersal, establishment and persistence in new ecosystems. Raphidiopsis raciborskii (Nostocales) is a successful invader of temperate ecosystems originating from the tropics that forms akinetes in their new habitats to overcome unfavorable winter conditions. In this study, we investigated akinete formation in R. raciborskii as a response to nitrogen limitation by exposing four genetically distinct strains to nitrogen-free medium. Cultures were maintained for 30 days at two temperature regimes, 20 °C (representing typical culture conditions) and 28 °C (mimicking hot summer conditions). All four strains started akinete formation within 3 days. However, we observed significant intraspecific variation in response to temperature, including differences in akinete abundance, maturation and size. Notably, vegetative cells continued to grow while akinetes were being formed, indicating the ability of R. raciborskii to simultaneously maintain growth and investment into dormancy. The pronounced strain-specific variation may provide adaptive advantages, enhancing the capacity of R. raciborskii to colonize diverse environments. Our results extend the concept of high intraspecific variability from the planktonic to the benthic phase. Understanding strain-specific dormancy strategies is crucial for predicting the ecological success and persistence of cyanobacteria under changing environmental conditions. These findings have important implications for bloom frequency, invasion dynamics, and the long-term establishment of these often-overlooked microbial invaders.